CRIMINAL CONFRONTATION FOR ASSAULTING FERTILIZED Ova "Destruction of fertilized Ova as a model" (Journal of Namibian Studies : History Politics Culture, 2023)
Scientific and medical development simulates reality and reflects its image as a natural inevitability and a necessity of life. However, the misconduct or abuse of the right that some biologists who specialize in this field may commit, or what is practiced by specialized doctors during their application of the technique of human reproductive fertilization, such as negligently or deliberately manipulating reproductive cells or destroying them, without adhering to observing the legal controls and ethical rules of the social system, which raises thorny and complex problems that result from criminal acts, which entail criminal liability. What requires creating a balanced relationship, caring for scientists and doctors, for the clear humanitarian services they provide and taking into account the application of the legal and Sharia rules that control and regulate them, in a manner consistent with the ethical system of society. This necessitates issuing a special law dealing with all these matters by stating what is permissible or not, with an indication of the penalties that are applied against the person who misbehaves in this field.